2022
DOI: 10.1111/1541-4337.13089
|View full text |Cite
|
Sign up to set email alerts
|

Dry surface biofilms in the food processing industry: An overview on surface characteristics, adhesion and biofilm formation, detection of biofilms, and dry sanitization methods

Abstract: Bacterial biofilm formation in low moisture food processing (LMF) plants is related to matters of food safety, production efficiency, economic loss, and reduced consumer trust. Dry surfaces may appear dry to the naked eye, however, it is common to find a coverage of thin liquid films and microdroplets, known as microscopic surface wetness (MSW). The MSW may favor dry surface biofilm (DSB) formation. DSB formation is similar in other industries, it occurs through the processes of adhesion, production of extrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 273 publications
(443 reference statements)
0
14
0
Order By: Relevance
“…Biofilm formation is affected by factors such as bacterial species, the characteristics of the surfaces, and the surrounding medium/environment [79,80]. In the food-processing industry, surface features are also very important for biofilm formation because they influence initial cell attachment [81]. Additionally, it has been observed that a critical surface tension value promotes bacterial adhesion [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…Biofilm formation is affected by factors such as bacterial species, the characteristics of the surfaces, and the surrounding medium/environment [79,80]. In the food-processing industry, surface features are also very important for biofilm formation because they influence initial cell attachment [81]. Additionally, it has been observed that a critical surface tension value promotes bacterial adhesion [82,83].…”
Section: Discussionmentioning
confidence: 99%
“…71,180,181 The adhesion of sticky food debris to these surfaces can encourage the attachment and colonization of bacteria. 34,182 Once bacteria establish biofilms, given their strong recalcitrance, they become notoriously difficult to remove. Thus, they may persist on food-processing machinery for months despite the frequent use of sanitation.…”
Section: Applications Of Nonwettable Coatings On Food-contact Surfacesmentioning
confidence: 99%
“…32 Standard testing methodologies to evaluate the durability and mechanical robustness of coated surfaces include sandpaper scratch testing, tape peeling, falling-sand abrasion, and blade scratching. Although a few studies have evaluated the strength and durability of certain coated surfaces using an ASTM standardized Taber test, 33,34 many others have adopted diverse nonstandardized custom-made abrading techniques. The random choice of abrasive sandpaper materials with different grit sizes, abrasion speed, weight load, and abrasion duration can make it difficult to accurately judge the overall performance between two surfaces.…”
Section: Durabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Dry sanitation techniques 7 or no-touch methods, including hot air, UV-C light, pulsed light, gaseous ozone (O 3 ), and NTP, have the potential to enhance the effectiveness of traditional methods (chlorine-based solutions), leading to more efficient sanitization processes. 5,8,9 Additionally, these approaches are environmentally friendlier than conventional wet methods, as they do not generate toxic waste such as acids and hydroxides usually employed in CIP processes, thus mitigating their environmental footprint.…”
Section: Introductionmentioning
confidence: 99%